Pelvic Fracture Care. (5th September 2018) - Gordon, Wade T; Fleming, Mark E; Johnson, Anthony E; Gurney, Jennifer; Shackelford, Stacy; Stockinger, Zsolt T
Abstract: While combat-related pelvis fractures are more commonly open, higher energy, and complex in pattern than those seen in the civilian setting, the principles of management are similar. The primary differences are related to the austere setting in which the initial management takes place, and the lack of resources typically available. Initial management consists of cessation of hemorrhage, along with the multi-disciplinary prioritized management of associated injuries, and skeletal stabilization. This is most commonly achieved with a compressive sheet or pelvic binder, with pelvic external fixation when resources allow, and debridement of open wounds as necessary. Definitive, internal fixation is delayed until the patient arrives at a higher echelon of care.